Censorship Policy of the Colorado Department of Corrections: A Case Study of Policy Implementation in a Gender Resistive Corrections Culture. Issue 4 (1st October 2016) - Jones, Susan J.
ABSTRACT: This case study research examined the censorship policy in the Colorado Department of Corrections. This examination included a review of current and past policies, interviews with current and former employees, interviews with subject matter experts regarding this policy, and an analysis of the organization's culture in which this policy process occurred. This policy change process was hampered by many barriers related to the workplace culture that was very resistive to adaptations for female employees. This case study proposes a theory of gender resistance in a corrections culture as a way to explain this policy change process.